All-optical frequency down-conversion based on cross-phase modulation in high nonlinearity dispersion-shifted fiber for WDM radio over fiber application - Yang, Hongwu; Sun, Junqiang; Du, Qiujiao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Simultaneous all-optical frequency down-conversion technique based on cross-phase modulation in a high nonlinearity dispersion-shifted fiber is proposed and verified by simulation, and its application to a wavelength-division-multiplexing (WDM) radio over fiber (ROF) is proposed. Error-free simultaneous all-optical frequency down-conversion of the 16 WDM ROF upstream channels is achieved. The simulated results show the performance of WDM signals is in good accordance with a single signal without any interference, and the power difference of two beat frequencies of the down-conversion signal is independent of the optical local oscillator power. The wavelength span of larger than 20 nm for down-conversion signal can be obtained.
Optica Applicata, Vol. 39, 2009, nr 1, s. 51-62
Keywords: optyka; radio over fiber (RoF); all-optical frequency down-conversion; wavelength division multiplexing (WDM); cross-phase modulation (XPM); modulation instability; high nonlin-earity dispersion-shifted fiber (HNL-DSF)